(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article systematizes the geospatial (GIS/RS) requirements for site selection and regional planning of solar and wind energy facilities in the Andijan region. A multi-criteria analysis (MCDA/AHP) approach is proposed based on digital orthophotos, remote sensing data, digital terrain model, and infrastructure layers. It is argued that the main technical requirements for the Fergana Valley are the accuracy of geospatial data, the update period, and interlayer compatibility (CRS/vertical datum) in the context of the relatively low solar radiation zone for the Fergana Valley, as well as the regional differentiation of wind resources. The results obtained provide practical recommendations on the geospatial data package, restriction zones, and evaluation criteria for RES facilities (PV/WE) in the Andijan region.